(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article explores the concept of alternative interrogative sentences in the English language. Alternative interrogative sentences are a unique form of questioning that offer multiple choices for responses. This article discusses the significance, structure, and formation of alternative interrogatives, providing examples to illustrate their usage.